Strategy 2030 achieving a prosperous, inclusive, resilient, and sustainable Asia and the Pacific. (Asian Development Bank, 2018)
Strategy 2030 sets the course for ADBs efforts to respond effectively to the Asia and Pacific regions changing needs.Asia and the Pacific has made great strides in poverty reduction and economic growth in the past 50 years. ADB has been a key partner in the significant transformation of the region and is committed to continue serving the region in the next phase of its development. Under Strategy 2030, ADB will expand its vision to achieve a prosperous, inclusive, resilient, and sustainable Asia and the Pacific, while sustaining its efforts to eradicate extreme poverty.